Combined Transplantation of Olfactory Ensheathing Cells With Rat Neural Stem Cells Enhanced the Therapeutic Effect in the Retina of RCS Rats - Zhai, Wei; Gao, Lixiong; Qu, Linghui; Li, Yijian; Zeng, Yuxiao; Li, Qiyou; Xu, Haiwei; Yin, Zheng Qin (Frontiers in Cellular Neuroscience, 2020)
Retinal degenerative diseases (RDDs) are the leading causes of blindness and currently lack effective treatment. Cytotherapy has become a promising strategy for RDDs. The transplantation of olfactory ensheathing cells (OECs) or neural stem cells (NSCs) has recently been applied for the experimental treatment of RDDs. However, the long-term outcomes of single-cell transplantation are poor. The combined transplantation of multiple types of cells might achieve better effects. In the present study, OECs (containing olfactory nerve fibroblasts, ONFs) and NSCs were co-transplanted into the subretinal space of RCS rats. By using ERG, immunofluorescence, western-blot and in-vitro transwell system, the differences in the electrophysiological and morphological changes of single and combined transplantation as well as the underlying mechanisms were explored 4, 8, and 12 weeks post-operation. Also, by using transwell system, the influence of OECs on the stemness of NSCs was discovered. Results showed that, compared to the single transplantation of OECs or NSCs, the combined transplantation of OECs and NSCs produced greater improvements in b-wave amplitudes in electroretinograms and the thickness of the outer nuclear layer at all three time points. More endogenous stem cells were found within the retina after combined transplantation. GFAP expression decreased significantly when NSCs were co-transplantated with OECs. Both the vertical and horizontal migration of grafted cells were enhanced in the combined transplantation group. Meanwhile, the stemness of NSCs was also better maintained after co-culture with OECs. Taken together, the results suggested that the combined transplantation of NSCs and OECs enhanced the improvement in retinal protection in RCS rats, providing a new strategy to treat RDDs in the future.